Bromatological characterization of cocoa shell (Theobroma cacao), from seven cantons of the Amazonia, Ecuador - Chafla, Ana F.; Rodríguez, Zoraya; Bocourt, R.; Torres, Verena (Cuban Journal of Agricultural Science, 2016)
In order to determine the variability of the bromatological composition of cocoa shells between Amazonia cantons, seven cantons were selected and, from each of them, three farms, according to their production and edaphoclimatic characteristics. For sampling, the "five points" method for plots lower than ten hectares was applied. Statistical relations by analysis of principal components and cluster were analyzed. The total variance indicated that with three principal components which was possible to explain 85.03% of the total variability. The principal component 1 (crude fiber, ether extract and nitrogen-free extract) was identified with the "energetic component", and explained 39.35% of the system variance. The principal component 2 (dry matter and ash) corresponded to the mineral component, and explained 26.2%. The principal component 3 was identified with the crude protein and explained 19.05%. The cut made in the dendrogram to interrupt the forming groups process, ranged 2.52, allowed to join four groups:1) comprising three cantons, characterized by a slight increase of dry matter and ash (90.30 and 9.09%); 2) a canton, with increase of ether extract, nitrogen-free extract and lower crude fiber content (3.61, 57.41, 21.95%); 3) two cantons, with crude protein increase of 8.97% and 4) two cantons with higher crude fiber content (24.93%). It is concluded that the bromatological composition of cocoa shells, from the seven cantons of the Amazonia, can be mainly differentiated by the contents of ether extract, nitrogen-free extract and crude fiber, but remains in the range described in the literature, so they would be good alternatives as substrates in the solid state fermentation processes. Key words: cocoa shell, energetic component, dendrogram.